2006
DOI: 10.1128/mcb.26.6.2430-2440.2006
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of the Cyclin-Dependent Kinase Inhibitor p21Cip1 on Serine 130 Is Essential for Viral Cyclin-Mediated Bypass of a p21Cip1-Imposed G1 Arrest

Abstract: Cip1 acts in a manner similar to that of p27 Kip1 , we have investigated the subversion of a p21 Cip1 -induced G 1 arrest by K cyclin. Here, we show that p21Cip1 is associated with K cyclin both in overexpression models and in primary effusion lymphoma cells and is a substrate of the K cyclin/cdk6 complex, resulting in phosphorylation of p21Cip1 on serine 130. This phosphoform of p21Cip1 appeared unable to associate with cdk2 in vivo. We further demonstrate that phosphorylation on serine 130 is essential for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 39 publications
(44 reference statements)
2
46
0
Order By: Relevance
“…KSHV also expresses a viral cyclin (K-cyclin) with functional properties of cellular D-and E-type cyclins (7,43). K-cyclin is resistant to inhibition by p21 and induces the phosphorylation of p21 at serine 130, resulting in the inactivation of p21 (7,20,40). We have independently confirmed that mutation of p21 serine 130 to alanine results in a p21 mutant protein that is a more potent inhibitor of cell cycle progression in BC-3 cells than wt p21 (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…KSHV also expresses a viral cyclin (K-cyclin) with functional properties of cellular D-and E-type cyclins (7,43). K-cyclin is resistant to inhibition by p21 and induces the phosphorylation of p21 at serine 130, resulting in the inactivation of p21 (7,20,40). We have independently confirmed that mutation of p21 serine 130 to alanine results in a p21 mutant protein that is a more potent inhibitor of cell cycle progression in BC-3 cells than wt p21 (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Phosphorylation at S130 was reported to either stabilize p21 (29) or promote its degradation (3,67). This modification was also proposed to cause p21 inactivation that was not attributed to degradation, but rather caused by its loss of cyclin/Cdk2 association (26). The p21 phosphorylation sites described above are conserved in both mice and humans.…”
Section: Kip2mentioning
confidence: 99%
“…21). Additionally phosphorylation of p21 on S130 (22) or T145 (23) negates its inhibition of cyclin/cdks and results in the restoration of cdk2 kinase activity in the presence of p21, as well as cell proliferation. These data suggest that modifications of p21 may change its functional activity.…”
Section: P21mentioning
confidence: 99%